The Effect of Ginger Candy Administration on First Trimester Pregnant Women with Emesis Gravidarum in the Working Area of the Kedung Banteng Community Health Center, Tegal Regency, 2025 - Battya, Annesya Atma; Rachman, Sylvia Meristika; Arieb, Rica; Shintami; Rosidah; Hendriyanti, Sri (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Emesis gravidarum is experienced by 50–80% of pregnant women in the first trimester and can develop into hyperemesis gravidarum if not treated properly. This condition carries the risk of dehydration, electrolyte imbalance, and fetal growth restriction. Ginger (Zingiber officinale) contains gingerol and shogaol, which have been proven to have antiemetic effects and are widely used as complementary therapy. To determine the effect of ginger candy on the degree of emesis gravidarum in pregnant women in their first trimester in the working area of the Kedung Banteng Community Health Center in Tegal Regency. Method: A pre-experimental design with a one-group pretest–posttest. The sample consisted of 20 pregnant women in their first trimester who experienced nausea and vomiting. The instrument used was the PUQE-24. Data were analyzed using the Shapiro-Wilk test and paired t-test. Result: Before the intervention, the average PUQE score was 9.20; after the intervention, it decreased to 7.00. The paired t-test results showed p=0.012, which means that there was a significant effect of ginger candy on the reduction of emesis gravidarum. Conclusion: Ginger candy is effective in reducing the severity of emesis gravidarum in first trimester pregnant women.